2018
DOI: 10.1080/03019233.2018.1443382
|View full text |Cite
|
Sign up to set email alerts
|

Modification of oxide inclusions in calcium-treated Al-killed high sulphur steels

Abstract: A study has been carried out to understand the modification of alumina inclusions in an Al-Killed high sulphur steel with calcium treatment in 150 tonne steel ladle. To avoid abnormalities during casting, inclusions chemistry needs to be controlled so that these inclusions are in liquid phase during continuous casting of steel. For calcium treatment to be effective, general practice is to desulphurise the steel so as to reach sulphur levels below 0.010% to prevent formation of solid CaS inclusions that are har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Although calcium treatment plays a role in modifying high melting point inclusions, with low Al 2 O 3 activity in the inclusions, elemental sulphur can react with calcium to form CaS inclusions. They are solid at casting temperatures and can be very detrimental to the steel quality [7,8]. For example, studies conducted by researchers [7][8][9] have demonstrated that CaS can be found in steel samples from billet [8] and hot-rolled plates [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although calcium treatment plays a role in modifying high melting point inclusions, with low Al 2 O 3 activity in the inclusions, elemental sulphur can react with calcium to form CaS inclusions. They are solid at casting temperatures and can be very detrimental to the steel quality [7,8]. For example, studies conducted by researchers [7][8][9] have demonstrated that CaS can be found in steel samples from billet [8] and hot-rolled plates [7].…”
Section: Introductionmentioning
confidence: 99%
“…They are solid at casting temperatures and can be very detrimental to the steel quality [7,8]. For example, studies conducted by researchers [7][8][9] have demonstrated that CaS can be found in steel samples from billet [8] and hot-rolled plates [7]. Additionally, Abdelaziz et al in 2009 [9] suggested that the formation of CaS may be largely associated with the addition of Ca to liquid steel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,5] Extensive studies have been performed on the characterization and control of inclusions in steels, involving the formation, modification, and removal of inclusions. [6][7][8][9][10][11][12][13][14][15] However, little attention was paid to study the variation of inclusions in solid steels during heating and rolling so far. [16][17][18][19] Significant variation in the composition of inclusions from the molten steel of continuous casting tundish to continuous casting products was reported.…”
Section: Introductionmentioning
confidence: 99%
“…The content of sulphur in steels is normally required to be extremely low. “Inclusion engineering” [ 3 ] could be one of the ways to reduce the harmful effects of sulphur [ 4 ] with a relatively low cost. However, implementation of this technique needs to well understand the basic thermodynamics behavior of sulphur in iron-based melts.…”
Section: Introductionmentioning
confidence: 99%